2007
DOI: 10.1007/s11745-007-3141-6
|View full text |Cite
|
Sign up to set email alerts
|

Direct Microwave Transesterification of Fingertip Prick Blood Samples for Fatty Acid Determinations

Abstract: Omega-3 polyunsaturated fatty acid (PUFA) dietary intakes and tissue levels are positively associated with various health benefits. The development of cost efficient, high throughput methodologies would enable research in large clinical and population studies, and clinical fatty acid profiling. Microwave heating for the transesterification of blood fatty acids was examined. Samples were collected by venous puncture and fingertip prick onto chromatography paper. Aliquots of serum, plasma, erythrocytes and whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 38 publications
(37 reference statements)
2
75
1
Order By: Relevance
“…Contrary to our findings with sphingomyelin, at least three previous studies have shown a reduced yield for very-long chain SFA and MUFA with the use of microwave-assisted transesterification both in serum/plasma and whole blood [1,6,16]. Most recently, two studies from one research group using a similar but multi-modal microwave system from the same company found yields of 70-90 % for 20:0, 22:0, 24:0 and 24:1n-9 [6] and 20-70 % for the same fatty acids in an earlier study [16].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our findings with sphingomyelin, at least three previous studies have shown a reduced yield for very-long chain SFA and MUFA with the use of microwave-assisted transesterification both in serum/plasma and whole blood [1,6,16]. Most recently, two studies from one research group using a similar but multi-modal microwave system from the same company found yields of 70-90 % for 20:0, 22:0, 24:0 and 24:1n-9 [6] and 20-70 % for the same fatty acids in an earlier study [16].…”
Section: Discussioncontrasting
confidence: 99%
“…Dried blood spots (DBS) collected by fingertip prick provide fatty acid determinations similar to venous whole blood sampling [1,2], and in recent years have gained in acceptance and been adopted for use in a variety of populations including infants [3,4], the elderly [5] and military personnel [6], among others [2,[7][8][9]. In addition, the % sum of eicosapentaenoic acid (EPA, 20:5n-3) + docosahexaenoic acid (DHA, 22:6n-3) in whole blood can be used as a predictor for risk of sudden cardiac death [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples were collected by fingertip prick, which has been shown to be an equally good measure of whole blood EPA and DHA as samples collected by conventional venous puncture 30 and reflective of dietary EPA and DHA intake. 31 Participants were asked to consume no food or beverage with the exception of water for 8 to 12 hours and no alcohol for 24 hours before blood sampling.…”
Section: Fingertip Prick Blood Samplesmentioning
confidence: 99%
“…Although a number of methods have been described for fatty acid profiling (Abdulkadir & Tsuchiya, 2008;Akoto, Vreuls, Irth, Pel, & Stellaard, 2008;Armstrong, Metherel, & Stark, 2008;Cantellops, Reid, Eitenmiller, & Long, 1999;Connerth, Grillitsch, Kofeler, & Daum, 2009;Glaser, Demmelmair, & Koletzko, 2010;Mazalli & Bragagnolo, 2007;Paterson & Amado, 1997;Quehenberger et al, 2011;RodriguezPalmero, Lopez-Sabater, Castellote-Bargallo, Dela Torre-Boronat, & Rivero-Urgell, 1997;Ulberth & Henninger, 1995;Wiesman & Chapagain, 2009), they often involve laborious procedures with several extraction steps and a combination of different solvents, anhydrous conditions and freezing cycles, which make sample preparation very time consuming. Moreover, the high sugar content in grape juice poses a significant problem to profile and quantify lipids at their trace levels due to the matrix effect.…”
Section: Introductionmentioning
confidence: 99%